Perspectives of Robotic Nursery from the Viewpoint of Hospital Management: German Evidence - Birgit LEHNER; Ivana BLAŽKOVÁ (Archives of Health Science and Research)
Objective: The objective of this study is to identify the perception of opportunities and risks by hospital managers with regard to the implementation of autonomous care robots in practice.